2019
DOI: 10.1007/s40801-019-00175-6
|View full text |Cite
|
Sign up to set email alerts
|

Drug Prescription in Older Swiss Men and Women Followed in Family Medicine

Abstract: Background We sought to estimate the prevalence of polypharmacy, the most prevalent drug classes involved, and the prevalence and type of potentially inappropriate prescribing among older male and female patients in family medicine. Methods We conducted a secondary analysis of baseline data from a pragmatic cluster-randomised trial on the efficacy of a screening and management tool for geriatric syndromes among older community-dwelling patients (aged ≥ 75 years) included by 42 family physicians. Information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
5
2
0
Order By: Relevance
“…Regarding sex differences, we found a higher rate of polypharmacy in women, consistent with the literature ( Guthrie et al, 2015a ; Schnegg et al, 2020 ). The difference was more pronounced at younger ages, and interestingly, hormonal contraceptives did not relevantly contribute to the difference.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding sex differences, we found a higher rate of polypharmacy in women, consistent with the literature ( Guthrie et al, 2015a ; Schnegg et al, 2020 ). The difference was more pronounced at younger ages, and interestingly, hormonal contraceptives did not relevantly contribute to the difference.…”
Section: Discussionsupporting
confidence: 91%
“…In this context, our polypharmacy prevalence of 20% in patients aged 41-64 years, consistent with findings from Scotland (Guthrie et al, 2015a), raises concerns that polypharmacy may be an important but underappreciated issue in this age group. For older patients, our findings are in line with those of two recent Swiss studies conducted in similar settings but with fewer GPs and patients (polypharmacy prevalence of 37% in a sample aged 75-80 years and of 60% in a sample aged over 75 years, respectively) (Aubert et al, 2016;Schnegg et al, 2020), as well as with general practice prescribing data from Scotland (Guthrie et al, 2015a). Moreover, two Swiss studies with a population-based sampling strategy and presumably less morbid patients than in our general practice-based study found lower polypharmacy rates compared to our results, as would be expected (Castioni et al, 2017;Schneider et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The Beers criteria have been used by investigators from many countries, including Canada, 71 Jordan, 40 Sweden, 41 Switzerland, 72 Brazil, 39 and the USA, 73 to explore how sex and gender might influence inappropriate prescribing. Most of these studies have reported that women are more likely than men to be prescribed medications that are potentially inappropriate.…”
Section: Reviewmentioning
confidence: 99%